AGROINDUSTRI KERUPUK RAMBAK DI DESA PANDAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR PROPINSI RIAU (STUDI KASUS PADA USAHA KERUPUK “GMC”) - Tibrani Tibrani; Kasman Karimi (Jurnal Ekonomi Sakti, 2023)
Small industry engaged in the agroindustry of rambak crackers of the type of rambak eats in Kampar Regency is in Pandau Jaya Village, Siak Hulu District, namely the small industry of “GMC” Rambak Crackers business. This business is the only agroindustry business that is developing quite well, has been operating for a long time, namely since 2011 until now. This study aims to analyze: 1) Entrepreneurial Characteristics and Business Profile of "GMC" Rambak Cracker Agroindustry in Pandau Jaya Village, Siak Hulu District, Kampar Regency. 2) Production Technology, Use of Production Inputs, and Production Processes in the "GMC" Rambak Cracker Agroindustry in Pandau Jaya Village, Siak Hulu District, Kampar Regency. 3) Production Cost, Production, Income, Value Added Rambak Cracker Agroindustry "GMC" in Pandau Jaya Village, Siak Hulu District, Kampar Regency. The method used in this research is the case study method. The results showed 1) The entrepreneur characteristics and business profile of the "GMC" rambak cracker agroindustry were 31 years old, 12 years of education, 9 years of business experience, 4 family dependents. Meanwhile, the average age of the workforce is 22 years, education is 9 years, business experience is an average of 1 year, and the number of family dependents is an average of 2 people. The business profile of the rambak cracker agroindustry is a family business that was established in 2011, with a small business scale, having a business license. The initial capital for the "GMC" rambak cracker agroindustry business came from own capital. 2) The production technology used to produce the output is by using simple technology. The use of tapioca flour is 75 kg/production process. The use of supporting materials per production process is wheat flour, garlic, salt, cooking oil, flavoring, ajinomoto, plastic size 12x20cm. The production process is carried out by entrepreneurs starting from the stages of kneading, printing, drying, frying and packing. 3) Production costs are Rp 1.507.438 with a total production of 70 kg, gross income of Rp 3.500.000/production process, net income of Rp 1.992.562/production process. The added value obtained is Rp 29.143/kg, with an R/C ratio of 2,32 which means the business is efficient.